Viability assessment of emerging smart urban para-transit solutions: Case of cab aggregators in Kolkata city, India - Anindya Basu (Journal of Urban Management, 2019)
The dimensions of transport development are closely linked with the socio-economic profile and technological level of a city. The entire trafficscape of the city of Kolkata evolved as the efficiency of the mass transport services declined, disposable income of the majority increased. There was gradual privatisation with increase in the share of para-transit modes. As the literate, technologically conversant urban population wanted a smarter alternative to regular taxis and auto rickshaws the app-based cab aggregator services brought in the silent revolution in the transport communication system. The main objectives of the paper are to bring out the essence of changing scenario, to access qualitatively and quantitatively that how far analysis of big data and reliance on technology through ICT and IoT has been able to meet the gap between expected and actual service delivery of the said para-transit mode through SWOT analysis, regression analysis and perception studies involving primary and secondary database and to have an idea about the future trajectory of this emerging app cab market. The study found that though majority of the commuters were satisfied with availability, reliability, cost effectiveness, safety, cashless option, driver behaviour, comfort and absence of bargaining there were issues regarding transparency and surge pricing. The drivers too were content with their improved earnings but were unhappy with the long hours and were apprehensive with regular incentive cuts. So, the situation is volatile with promising future if the companies manage to balance between the virtual capabilities and actual reality.
Keywords: 710; Para-transit; App cab aggregators; Technology; Big data; ICT; IoT